Failing Cityscape: Urbanization and Urban Climate - Choudhary, Bikramaditya K.; Tripathi, Arun K. (National Geographical Journal of India, 2022)
India is getting fast urbanized. With the rapid increase in urban population and consequent consumption the pollution scenario is moving in a direction that is detrimental to healthy living. Studies related to micro climate in general and urban climate in particular has become new research focus over last few decades. Cities are key site where climate change is being addressed. In this article we are trying to cover the changing pattern of urban environ over time with special case study of Delhi. Who is the most vulnerable to the climate change and at what effect? Excessive use of modern technology and improper management by municipality in current scenario has led the change in climate drastically. As a result floods are seen in some areas even low rainfall while smog in and around the cities, often termed as 'extreme weather event'. Further, normal natural phenomenon, like mist or fog become toxic and makes lives in the cities unliveable. Privatisation of transportation, constructions etc. also aggravate the environmental degradation. Private company either neglect or wilfully ignore to consider the Environment Impact Assessment (EIA) in comparison of government bodies. The theme has an extremely vast application; we will just discuss the effects of human on the climate or urban climate to be specific.